(3QSGdI aj GdehGQjKs - (3eLghds
(3ChdgG (B:s
... (3ef HYO hUjI JhUhf HgG Gh Ojf hddUMjM ef GdCNHGQ hddELeGY , hhdGA HaJM GdhGh hgh aj GddZI ejQGK ddYJb HaJM GdJGA ddeYJb HcSQgG haj GdTQY (B... (3hZjQg aGdRhLGf jONdGf Ydi LejY GdWHbGJ (B...s
(3BNQgG (B:s
... (3hefgG jUM hddCfKi SJhf hddNfKi JSYhf hdCMO GdCHhjf ef MUI GdNfKi SHYI YTQ ef MUI GdCfKi GKfG YTQ eLehY Pdc JSYI hYTQhf ddCfKi KeGfjI hCQHYhf hddNfKi KdGK hSHYhf (B...s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3abg GdePGgH GdCNQis